Lower Urinary Tract Symptoms Before and After Simple Abdominal Hysterectomy in a Selected Tertiary Hospital - Jahan, Muna Shalima; Billah, Syed Muhammad Baqui (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Objective: To assess lower urinary tract symptoms (LUTS) before and after simple abdominal hysterectomy. Methods: This quasi-experimental study was conducted in Bangabandhu Sheik Mujib Medical University, Dhaka on respondents who were waiting for simple abdominal hysterectomy for beneign gynaecological problems. LUTS and ultrasonic and uroflowmetric findings were assessed on 48 patients before simple abdominal hysterectomy (SAH) followed by reassessment of symptoms on 33 patients and uroflowmetric assessment on 27 patients within 3-4 months after SAH. Results: Thirty percent urgency (p=0.02), 18% urge incontinence (p=0.03), 42% stress incontinence (p=0.001), 24% dysuria (0.02), 33% stress on cough or vulsalva (p=0.001), 27% delayed bladder emptying (p=0.04) and 30% sensation of residual urine (0.01) was improved significantly after SAH while around 18% urinary frequency (p=0.07) was almost significantly improved. None of the patients complained of nocturia after SAH. As for urodynamic assessment, there was significant increase in maximum bladder capacity (p<0.001), decrease in bladder wall thickness (p<0.001) and decrease in average flow rate (0.04) though there was no significant decrease in post void residue. Overall there had been a considerable decrease of all pre operative symptoms from nearly 82% to 37% post operatively. Conclusions: There was significant improvement of voiding symptoms following SAH as well as improvement of ultrasongraphic findings and uroflometric features. J Bangladesh Coll Phys Surg 2015; 33(1): 7-11